Revisão de alguns aspectos da paisagem cultural de Teófilo Otoni, na mesorregião do Vale do Mucuri, Minas Gerais - Brasil - Duarte Araújo Pereira, Larissa; Barbosa Caldeira, Altino; Conceição Barroso, Leônidas (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
This article presents some aspects of the cultural landscape of the municipality of Teófilo Otoni, located in the mesoregion of the Mucuri Valley, in Minas Gerais. It specifically addresses the municipality’s location, its history of settlement, the current presentation of the built landscape, biome, soil, water resources, society, and culture. This work is part of the doctoral bibliographic research of the Laboratory of Studies of the Mucuri Valley at the Pontifical Catholic University of Minas Gerais (PUC Minas).